2015
DOI: 10.1016/j.jvs.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Rates and predictors of readmission after minor lower extremity amputations

Abstract: OBJECTIVES One goal of the Patient Protection and Affordable Care Act is to reduce hospital readmissions, with financial penalties applied for excessive rates of unplanned readmissions within 30 days among Medicare beneficiaries. Recent data indicate that as many as 24% of Medicare patients require readmission following vascular surgery, although the rate of readmission following limited digital amputations has not been specifically examined. The present study was therefore undertaken to define the rate of unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 19 publications
4
24
0
1
Order By: Relevance
“…Several authors have reported rates of readmission after individual vascular procedures, such as abdominal aortic aneurysm repair (8%-54%), [14][15][16] amputation (9%-18%), [17][18][19] and lower extremity bypass (12%-49%). 8,9,11,20,21 However, there are conflicting reports regarding readmission rates and reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported rates of readmission after individual vascular procedures, such as abdominal aortic aneurysm repair (8%-54%), [14][15][16] amputation (9%-18%), [17][18][19] and lower extremity bypass (12%-49%). 8,9,11,20,21 However, there are conflicting reports regarding readmission rates and reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Lower limb amputations account for 85% of this total and have a major socioeconomic impact, with loss of the capacity to work, of socialization, and of quality of life, in addition to complications such as hematoma, infections, necrosis, contractures, neuromas, phantom pain, and re-admissions, making them a considerable public health problem. [2][3][4] Overall, 80% of all lower limb amputations are performed on adults. The main associated risk factors are diabetes mellitus, arterial hypertension, smoking, dyslipidemia, advanced age, chronic renal failure, hypercoagulability, and genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Past research on the association between smoking status and readmission rates has produced equivocal results. [26][27][28][29][30][31][32][33][34] Many studies have examined commonly collected demographic variables. It has been reported that increasing age could potentially serve as a predictor of all-cause hospital readmissions, especially in patients over the age of 65.…”
Section: Discussionmentioning
confidence: 99%